A review of diagnosis of Duchenne and Becker muscular dystrophy - Dana Chunkayeva; Altynshash Jaxybayeva (National Scientific Medical Center, 2021)
Duchenne muscular dystrophy and Becker muscular dystrophy are progressive serious neuromuscular disorders. We have reviewed contemporary data on diagnosis of DMD and BMD. Searches were carried out from 2010 to 2020. This article discusses clinical signs, features in biochemical blood analysis, findings on instrumental investigation, various mutations causing DMD/BMD, indications for morphological examination of muscles available for setting up the diagnosis for children suspected of DMD/BMD.